A SURVEY ON THE GLOBAL SUCCESS OF THE ISLAMIZATION OF KNOWLEDGE PROGRAMME WITH PARTICULAR REFERENCE TO NIGERIA - Adebayo, Rafiu Ibrahim (Journal of Al-Tamaddun, 2012)
The contemporary Islamization of knowledge programme is a global intellectual programme aimed at re-orientating and recasting the corpus of human knowledge to conform to the Islamic belief system and worldview. The thrust of this paper is therefore to establish the extent this programme has gone and the level of its practicability at global level but with particular reference to Nigeria. This paper discusses the conceptual meanings of the term ?Islamization of knowledge? and the extent of acceptability of the programme in the various educational institutions. Suggestions on how the programme could better be handled to enhance effectiveness are equally made